A Socio-Legal Analysis of Public Policy Implementation in Community Empowerment Through Social Forestry : A Case Study of LPHD Puwesu, East Luwu Regency - Andi Muhammad Idin; Mustaming Mustaming; Takdir Takdir (International Journal of Educational Administration, Management, and Leadership, 2025)
This study examines the sociological and juridical dimensions of community empowerment through the social forestry scheme implemented at LPHD Puwesu, East Luwu Regency, Indonesia. Forest management in Indonesia has long faced various challenges, including illegal logging, land conversion, tenure conflicts, and limited community access to forest resources. Social forestry has emerged as a strategic policy to promote sustainable forest management while improving local community welfare. This study aims to analyze the implementation of the social forestry scheme, identify supporting and inhibiting factors, and examine its contribution to community empowerment in the forest area. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving LPHD administrators, local government officials, forestry extension officers, and community members. The findings reveal that the social forestry program at LPHD Puwesu has strengthened community participation, improved legal access to forest management, and enhanced environmental awareness among local residents. However, the implementation still faces challenges related to limited human resources, institutional capacity, funding, and community understanding of sustainable forest management. The study concludes that social forestry serves as an important instrument for participatory and sustainable forest governance while also functioning as a mechanism for community empowerment and legal recognition of local forest management practices.